KEHUJAHAN HUKUM NEGARA SEBAGAI SUMBER HUKUM ISLAM (STUDI KASUS LEGALITAS KOMPILASI HUKUM ISLAM DI INDONESIA ) - M.Fadhlan Is (Program Studi Hukum Keluarga Islam STAIN Mandailing Natal, 2021)
The formulation of the problem in this study is how is the violation of state law as a source of Islamic law and whether the Compilation of Islamic Law has fulfilled the requirements to become state law This research was conducted through a qualitative research library (library research) and comparative analysis. While the method used to analyze the data is induction and deduction which are then compared, to draw conclusions as answers to the problems that have been formulated. The author finds the fact that in establishing shari'a law' in classical times, many local ijmak practices were found, namely the stipulation of syar'i law was agreed upon and carried out by only a few mujtahids and only covered one particular area. Looking at the facts and conditions of Muslims who adhere to the